Survival Analysis and Factors Associated with Pulmonary Tuberculosis - Zul Adhayani Arda; Sunarti Hanapi Nur; Nur Hamdani Nur; Sabrina Nadjib Mohamad; Mohammad Amon (Journal of Public Health and Pharmacy)
Introduction: Analysed the survival rates of patients and factors associated with pulmonary tuberculosis at the Limboto Public Health Center, with particular attention to the role of hypertension as a predictor of treatment failure and its potential integration into TB treatment guidelines.